The Portuguese Online Knowledge Library (B-on): a year of academic research at Portucalense University - Nunes, Manuela Barreto (2015)
“B-on” is the electronic resources platform acknowledged by the Portuguese scientific community, providing a high number of scientific resources and electronic services. Portucalense University adhered to B-on in 2013. After a year, a study of use and evaluation of the professors’ satisfaction was conducted. This paper presents the results obtained through the application of a questionnaire and the analysis of statistical data supplied by the platform. Results reveal a medium level of compliance, although with high intensity and users’ satisfaction. More information literacy instruction is required in order to amplify and diversify the use of the tool.